Case Report: Suppurative Labyrinthitis Induced by Chronic Suppurative Otitis Media - Xiao, Qianwen; Zhang, Yuzhong; Lv, Jingrong; Yang, Jun; Zhang, Qing (Frontiers in Neurology, 2022)
A discussion on suppurative labyrinthitis associated with chronic suppurative otitis media (CSOM) may seem to be an outdated issue due to the advent of antibiotics in the last century. In previous literature, limited cases of suppurative labyrinthitis have been reported. This case, therefore, is an excellent and rare opportunity to study its clinical symptoms, diagnosis and treatments. This report described the case of a 39-year-old female with a history of CSOM for 20 years, and she often presented with otorrhea, vestibular disorder and hearing impairment. Computed tomography (CT) of the temporal bone revealed fistulae in both the basal turn of the cochlea and the horizontal semicircular canal. Combining with otolaryngology examination results, suppurative labyrinthitis was considered. During a three-month follow-up, her symptoms were improved significantly after surgery. In conclusion, suppurative labyrinthitis must not be overlooked and neglected, early diagnosis and treatments are of vital importance.